Non-invasive Investigation of Human Hippocampal Rhythms Using Magnetoencephalography: A Review - Pu, Yi; Cheyne, Douglas O.; Cornwell, Brian R.; Johnson, Blake W. (Frontiers in Neuroscience, 2018)
Hippocampal rhythms are believed to support crucial cognitive processes including memory, navigation and language. Due to the location of the hippocampus deep in the brain, studying hippocampal rhythms using non-invasive magnetoencephalography (MEG) recordings has generally been assumed to be methodologically challenging. However, with the advent of whole-head MEG systems in the 1990s and development of advanced source localization techniques, simulation and empirical studies have provided evidence that human hippocampal signals can be sensed by MEG and reliably reconstructed by source localization algorithms. This paper systematically reviews simulation studies and empirical evidence of the current capacities and limitations of MEG “deep source imaging” of the human hippocampus. Overall, these studies confirm that MEG provides a unique avenue to investigate human hippocampal rhythms in cognition, and can bridge the gap between animal studies and human hippocampal research, as well as elucidate the functional role and the behavioural correlates of human hippocampal oscillations.